Peningkatan Hasil Belajar PJOK Materi Permainan Bola Voli Peserta Didik melalui Model Discovery Learning di Kelas V SD Negeri 03 Payakumbuh Semester Ganjil T.P 2022/2023 - Marianto Marianto (Journal on Education, 2022)
This study aims to see and analyze the increase in PJOK learning outcomes of students through the discovery learning model in Class V SDN 03 Payakumbuh odd semester TP 2022/2023." This research was conducted using the Classroom Action Research method which consisted of three cycles, where each cycle consisted of; planning, action, observation and reflection. It will be carried out from July to December 2022. Data is processed in each cycle and then analyzed using percentages. The results obtained from this study are that using the Discovery Learning model can improve student PJOK learning outcomes. This is evident from the increase in student learning outcomes in each cycle. The conclusion obtained from this study is that the use of the Discovery Learning Model can improve student learning outcomes.